Audit of financial lease - E. A. Gubaidullina; K. Z. Akhmetshina (Путеводитель предпринимателя)
The article researches the issue of audit of a Finance lease, the principles of financial audit, but also identified a number of advantages of financial lease to other investment mechanisms. The result of the work done is the conclusion that in modern Russia the development of financial leasing operations hampered by many unresolved issues, such as legal, accounting and tax aspects of the financial lease.